kondisi sosial ekonomi pekerja pada pabrik PT perkebunan pelalu raya di Nagari Salareh Aia Kecamatan Palembayan Kabupaten Agam - Novia Rusadi; Afdhal Afdhal (JURNAL BUANA, 2019)
ABSTRAK This study aims to find out: (1) Income level, (2) Conditions of education, (3) Conditions of residence, (4) Ownership of living facilities of workers at the PT. Greater Plantation in Nagari Salareh Aia, Palembayan District, Agam Regency. This type of research is quantitative descriptive. The study population was all workers at the PT. Pelalu Raya Plantation in Nagari Salareh Aia, Palembayan District, Agam District, which consists of 170 people. Sampling in this study was carried out using the Slovin formula, the technique used was Proportional Random Sampling, so that 63 respondents were obtained. Data collection techniques are carried out by observation of questionnaires and documentation. The data analysis technique used is percentage. The results of the study indicate that: (1) The level of income of workers at the PT. Great Plantation of Rp. 2,500,000 - Rp. 3,500,000 per month (63.4%). (2) The level of education of workers at the PT. Pelalu Raya Plantation has been classified as good, where most of the workers have graduated from high school (61.9%) in addition there are some people who have gone through tertiary education (12.6%), for the education of working children at this time most of the children from workers are taking education in junior high school (31.3%). (3) Workers' living conditions have met the minimum area, which is an average of 10.7 m² / person (65%), with permanent housing types (85.7%), and each house is equipped with electricity. (4) the ownership of living facilities (motorbikes) of the majority of workers already have 1 motorbike (85.7%), for the ownership of living facilities (cars) most of the workers do not have a car, but there are some people who have 1 cars (7.9%). Keywords: Socio-Economic Condition of Factory Workers